problems facing educational research in the Ministry of Education (Journal of the College of Basic Education, 2022)
The nature of education requires that educational research address many and varied problems.It is related to other sciences and knowledge that it makes use of in many cases to achieve its goals. Regulatory issuesThe intertwining of disciplines in educational research is linked to the crisis of the identity of specialization and scientific research, whichInvolves the tension between the professional identity of the field and the professional, professional and individual identity of the researcher.The one who is involved in a permanent struggle that leads to loyalty to his scientific